Microstructural and defect characterization in single beads of the CrMnFeCoNi high-entropy alloy processed by the multi-beam laser directed energy deposition - Kholqillah Ardhian Ilman; Yorihiro Yamashita; Takahiro Kunimine (Journal of Advanced Joining Processes)
This study investigates the microstructural characteristics and defect formation in single beads of the CrMnFeCoNi high-entropy alloy (HEA) processed by the multi-beam laser directed energy deposition (MBL-DED). The research aims to understand how the MBL-DED process can effectively control the bead formation with meltpool or without meltpool by leveraging the multi-beam laser focusing position in the MBL-DED system, and maintain the equiatomic balance of the HEA deposited on substrate surfaces by controlling the bead formation without meltpool and addressing potential defects. The formation of meltpool typically leads to mixing between the base material and the deposited HEA bead, altering the equiatomic balance and reducing the alloy's ability to stabilize the solid-solution phase. The multi-beam laser focusing position of the six laser beams of the MBL-DED system was adjusted to 0.5 mm above the substrate surface, with varying laser powers (80–160 W) and scanning speeds (10–40 mm/s). Hereafter, this laser geometry is called as overfocusing position, ∆f, of 0.5 mm. This method shifted the process dynamics from a conventional meltpool formation to a thin reaction layer formation (no-meltpool formation). At a laser power of 140 W and a scanning speed of 30 mm/s, the absence of meltpool was observed. However, at 120 W, bead discontinuity increased with higher scanning speeds. Additionally, higher speeds and lower powers resulted in increased porosity, supported by partially melted and unmelted powder. Microstructural analysis revealed that increasing scanning speeds reduced grain size, transitioning from larger and uniform grains to finer and irregular grains. This research demonstrates the potential of the MBL-DED system in optimizing the HEA powder processing by controlling meltpool formation and mitigating defects, and in contributing to open up a new joining processing technology with less reaction layer through additive manufacturing.